Implementasi Kebijakan Pajak Reklame Dalam Meningkatkan Penerimaan Pajak Daerah Pada Suku Dinas Pelayanan Pajak Kota Administrasi Jakarta Barat - Purwaningtias, Agitta Sofyan (Publika : Jurnal Administrasi Publik, 2021)
This study aims to determine the implementation of policies in the advertising tax increase local tax revenue as well as to determine the obstacles that exist in improving the advertisement tax. This study uses a qualitative approach with descriptive analysis method which means explaining the data and the facts accurately and systematically. Samples taken are reports revenue plan and actual revenues Advertising Tax Rate Tax Office In West Jakarta Administration Year 2015-2016. The results showed that in the year 2015-2016 advertisement tax acceptance was not optimal due to the advertising tax revenue realization is still considered low and the determination of the target too high and unrealistic to tax revenues advertisement. Based on this, Better Local Government Policy Before Removing supposed to socialize in advance, as well as coordinating with the parties concerned with the advertisement tax hike before the policy rule Value Rent Advertisement issued, so it will not burden the taxpayer. Provides strict sanctions to the organizers of illegal billboards.Â Keywords: policy implementation, advertisement taxÂ